2010
DOI: 10.1111/j.1476-4431.2010.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an indirect oscillometric blood pressure monitor in normotensive and hypotensive anesthetized dogs

Abstract: The oscillometric device was not reliably predictive of intra-arterial BP during hypotension associated with acute hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 16 publications
2
43
1
8
Order By: Relevance
“…In the study by Shih et al. (2010) another type of oscillometric blood pressure monitor (petMAP; Ramsey, Medical Inc, FL, USA) greatly overestimated blood pressure measurements when hypotension was present, an indication that this device is not a good substitute for invasive blood pressure measurement technique in hypotensive dogs.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Shih et al. (2010) another type of oscillometric blood pressure monitor (petMAP; Ramsey, Medical Inc, FL, USA) greatly overestimated blood pressure measurements when hypotension was present, an indication that this device is not a good substitute for invasive blood pressure measurement technique in hypotensive dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The patient of this report also developed significant hypotension during anesthesia, and this likely contributed to the renal damage, but it was unlikely to have been the sole cause, especially since azotemia developed before anesthesia. The degree of hypotension in this patient may have been over‐ or underestimated, as oscillometric blood pressure has been shown to be unreliable in anesthetized hypotensive dogs . While hypotension is a well reported contributor to the onset of AKI, the magnitude and duration of hypotension required to trigger damage to the kidney is unknown and is most likely multifactorial.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, Heard et al (38) disagreed with these results regarding relationship between non-invasive & invasive as they analyzed ABP data obtained by noninvasive method and found variation in results when compared with invasive method. Furthermore, Acierno et al (39) Shih et al (40) and Almeida (41) found a difference between the two methods. Based on that critical care nurses are responsible for monitoring patients' hemodynamical status and reporting any deviation from normal, they have to know the effect of certain drugs on vital signs to obtain hemodynamic stability.…”
Section: Discussionmentioning
confidence: 98%